Recommendations for SARS-CoV-2/COVID-19 testing: a scoping review of current guidance. Issue 1 (6th January 2021) - Arevalo-Rodriguez, Ingrid; Seron, Pamela; Buitrago-García, Diana; Ciapponi, Agustin; Muriel, Alfonso; Zambrano-Achig, Paula; del Campo, Rosa; Galán-Montemayor, Juan Carlos; Simancas-Racines, Daniel; Perez-Molina, Jose A; Khan, Khalid Saeed; Zamora, Javier
Abstract : Background: Testing used in screening, diagnosis and follow-up of COVID-19 has been a subject of debate. Several organisations have developed formal advice about testing for COVID-19 to assist in the control of the disease. We collated, delineated and appraised current worldwide recommendations about the role and applications of tests to control SARS-CoV-2/COVID-19. Methods: We searched for documents providing recommendations for COVID-19 testing in PubMed, EMBASE, LILACS, the Coronavirus Open Access Project living evidence database and relevant websites such as TRIP database, ECRI Guidelines Trust, the GIN database, from inception to 21 September 2020. Two reviewers applied the eligibility criteria to potentially relevant citations without language or geographical restrictions. We extracted data in duplicate, including assessment of methodological quality using the Appraisal of Guidelines for Research and Evaluation-II tool. Results: We included 47 relevant documents and 327 recommendations about testing. Regarding the quality of the documents, we found that the domains with the lowest scores were 'Editorial independence' (Median=4%) and 'Applicability' (Median=6%). Only six documents obtained at least 50% score for the 'Rigour of development' domain. An important number of recommendations focused on the diagnosis of suspected cases (48%) and deisolation measures (11%). The most frequently recommended test was the reverse transcription-PCR (RT-PCR) assay (87 recommendations) and the chest CT (38 recommendations). There were 22 areas of agreement among guidance developers, including the use of RT-PCR for SARS-Cov-2 confirmation, the limited role of bronchoscopy, the use chest CT and chest X-rays for grading severity and the co-assessment for other respiratory pathogens. Conclusion: This first scoping review of recommendations for COVID-19 testing showed many limitations in the methodological quality of included guidance documents that could affect the confidence of clinicians in their implementation. Future guidance documents should incorporate a minimum set of key methodological characteristics to enhance their applicability for decision making.